2014
DOI: 10.1002/ejic.201400030
|View full text |Cite
|
Sign up to set email alerts
|

Nitrile‐Supported Coordination Polymers of Cerium(III) Bromide

Abstract: A series of nitrile-supported coordination polymers of cerium bromide (CeBr 3 ) are reported, including adducts of trimethylacetonitrile, benzonitrile, and glutaronitrile. The identities of the compounds are established on the basis of single-crystal X-ray diffraction data, and the compounds are further char-[a]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Importantly, the structural characterization of 6 ·MeCN provides the first example of an unambiguous homoleptic cerium MeCN complex. Like complex 5 ·MeCN, the Ce center is also in a tricapped trigonal-prismatic geometry and the average Ce–N bond distance [2.61(1) Å] is consistent with those of 2 ·2MeCN and other cerium MeCN solvates. , Last, while complex 7 ·MeCN is the third reported homoleptic MeCN solvate of neodymium, , it is the first to provide complete X-ray crystallographic data for structural analysis, where the average Nd–N bond distance [2.57(1) Å] is consistent with other Nd–N MeCN interactions. , …”
Section: Resultsmentioning
confidence: 65%
See 2 more Smart Citations
“…Importantly, the structural characterization of 6 ·MeCN provides the first example of an unambiguous homoleptic cerium MeCN complex. Like complex 5 ·MeCN, the Ce center is also in a tricapped trigonal-prismatic geometry and the average Ce–N bond distance [2.61(1) Å] is consistent with those of 2 ·2MeCN and other cerium MeCN solvates. , Last, while complex 7 ·MeCN is the third reported homoleptic MeCN solvate of neodymium, , it is the first to provide complete X-ray crystallographic data for structural analysis, where the average Nd–N bond distance [2.57(1) Å] is consistent with other Nd–N MeCN interactions. , …”
Section: Resultsmentioning
confidence: 65%
“…Like complex 5•MeCN, the Ce center is also in a tricapped trigonal-prismatic geometry and the average Ce−N bond distance [2.61(1) Å] is consistent with those of 2• 2MeCN and other cerium MeCN solvates. 5,47 Last, while complex 7•MeCN is the third reported homoleptic MeCN solvate of neodymium, 4,39 it is the first to provide complete Xray crystallographic data for structural analysis, where the average Nd−N bond distance [2.57(1) Å] is consistent with other Nd−N MeCN interactions. 48,49 Complexes 5−7 were further characterized by CHN EA and IR spectroscopy.…”
Section: ■ Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Multiple studies showed that the molecular structures of lanthanide halide complexes highly depend on the donor solvent used in the synthesis. , Coordination of small donor molecules mainly leads to mononuclear complexes. Most often, tetrahydrofuran (thf) or dimethoxyethane (dme) are used in the synthesis and fill up the coordination sphere; , pyridine or acetonitrile , are also frequently used. Hereinafter, we use “solvate” to denote a complex with coordinated solvent molecules.…”
Section: Introductionmentioning
confidence: 99%
“…Our group has recently developed coordination polymers of cerium(III) bromide with ligands coordinated through a nitrile group [26]. Functionalizing the pore surfaces within the mesoporous silica with a nitrile group should allow cerium bromide to bind to the matrix by forming nitrile coordination compounds at the pore surface.…”
Section: Introductionmentioning
confidence: 99%